Pomen klinične ocene bolnika z nestabilno angino pektoris med stenokardijo za napoved poteka bolezni - Bajuk, Katica (Medicinski razgledi, 2001)
Unstable angina pectoris (UAP) and non-ST elevation myocardial infarction (NSTEMI) signify a critical moment of coronary artery disease. The choice of appropriate therapy depends on the estimated risk of adverse outcome. Risk assessment is made primarily on the basis of typical changes in the electrocardiogram and values of biochemical markers of cardiac muscle damage (troponine T and I, enzymes of cardiac muscle necrosis). Only a limited numberof studies included clinical characteristics in the risk estimates of such patients, but none of these studies considered clinical presentation during stenocardia. The aim of our research was to evaluate the prognostic value of clinical characteristics during stenocardia. The clinical presentation of a patient with UAP/NSTEMI during stenocardia predicts the adverse outcome of the disease during in-hospital treatment. A retrospective analysis was performed on patients with an admission diagnosis of UAP/NSTEMI who were admitted to the Center for Intensive Internal Medicine between January and December 1999. The following parameters were selected for describing the patients clinical presentation: age, duration of stenocardia, systolic blood pressure and heart rate during stenocardia. The connection of these characteristics with an adverse outcome of the illness (death, acute myocardial infarction, urgent revascularization procedure) up until discharge from the hospital was analyzed using analysis of variance and multiple logistic regression. One hundred ninety-two patients, aged 40-96, were included. Seven (3.6%)of the patients died, 16 (8.3%) suffered a myocardial infarction, and 82 (42.7%) underwent urgent revascularization. Death of the patients before discharge from the hospital was significantly correlated with their systolic blood pressure (p=0.01) and heart rate (p<0.001) during stenocardia. (Abstract truncated at 2000 characters).
Keywords: Angina nestabilna; Angina, unstable; Complications; Miokardni infarkt; Elektrokardiografija; Myocardial infarction; Enote za intenzivno medicino; Mortality; Krvni pritisk; Prognosis; Miokardna revaskularizacija; Electrocardiography; Intensive care units; Prognoza; Srce, frekvenca; Age factors; Blood pressure; Starostni faktorji; koronarna bolezen; Heart rate; Myocardial revascularization; angina pectoris; diagnostika